2020
DOI: 10.1111/eva.13039
|View full text |Cite|
|
Sign up to set email alerts
|

The role of host environment in cancer evolution

Abstract: Somatic mutations in oncogene and tumor suppressor genes accumulate in healthy tissues throughout life and delineate clones with limited expansion. Lifestyle‐related toxic insults increase the size and number of these clones that participate to tissue aging. Their identification has blurred the boundaries between clonal expansion and malignant tumor and has drawn more attention to the role of the host environment in tumor emergence and progression. Local tissue factors such as disrupted cell interactions and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 194 publications
0
14
0
Order By: Relevance
“…The TiDiS theory can be viewed as an alternative explanation to the overly autonomous "chromosome-centric" standard model. This causal concept strongly supports MM (in particular, but cancer in general) not only as an evolutionary multistep process but also as an ecological (environmental tissue dependent) process in which a critical initiating/promoting role is devoted to an environmental niche of significance and its disruption [19][20][21].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…The TiDiS theory can be viewed as an alternative explanation to the overly autonomous "chromosome-centric" standard model. This causal concept strongly supports MM (in particular, but cancer in general) not only as an evolutionary multistep process but also as an ecological (environmental tissue dependent) process in which a critical initiating/promoting role is devoted to an environmental niche of significance and its disruption [19][20][21].…”
Section: Introductionmentioning
confidence: 63%
“…We would like to go further by providing a theory giving bone/BME a potential role in the initiation of MM, which may ultimately lead to therapeutic perspectives. Several arguments can now be formulated against a unique initiating role of genetic alterations because alterations of the host environment could also contribute to the emergence of tumors [21]. For instance, oncogenic mutations are not sufficient to start transformation; oncogenesis can initiate from disruption of the BME, and cancer cells harboring multiple genetic alterations can be controlled and reverted by a healthy tissue environment [21,[63][64][65].…”
Section: General Scheme Of the Tidis Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…If genetic alterations are already present, they would accelerate the process, but it can be considered that the process can start without driver mutations. Multiple examples showed that oncogenic mutations are not sufficient to start transformation ( Martincorena et al., 2015 ; Yizhak et al., 2019 ; Yokoyama et al., 2019 ), that oncogenesis can initiate from disruption of the micro-environment ( Kode et al., 2014 ; Maffini et al., 2004 ; Raaijmakers et al., 2010 ; Walkley et al., 2007 ), and that cancer cells harboring multiple mutations can be controlled and reverted by a healthy tissue environment ( Booth et al., 2011 ; Bussard et al., 2010 ; Hochedlinger et al., 2004 ; Rubin, 2006 ; for review, see Solary and Lapane, 2020 ).…”
Section: Significance For Oncogenesis: Return Of Metazoan Cells To Unmentioning
confidence: 99%
“…We define driver events as discrete molecular alterations that provide the cancer cell of origin and the resulting clone the necessary means to overcome both the intracellular and extracellular tumor suppressor mechanisms, such as cell cycle checkpoints, contact inhibition, immune surveillance, and promote growth in the absence of growth factors. Thus, our concept of a driver event integrates mutational, microenvironmental, immune and evolutionary perspectives ( Rozhok & De Gregori, 2015 ; Solary & Lapane, 2020 ). It is also important to note that only the winner clone’s evolutionary history determines the time of tumour appearance and thus the kinetics of cancer incidence; therefore, any mention of driver events in this article would always refer to driver events in the winner clone.…”
Section: Introductionmentioning
confidence: 99%